Rapid stability-indicating UHPLC method for determination of lamivudine and tenofovir disoproxil fumarate in fixed-dose combination tablets - de Souza, Danielle Evangelista Rabelo; Gomes, Nicoly Kaliny Magela; Pianetti, Gerson Antônio; Pereira, Bruno Gonçalves; Fernandes, Christian (Drug Analytical Research, 2026)
Lamivudine (3TC) and tenofovir disoproxil fumarate (TDF) are antiretroviral drugs widely used for AIDS treatment. Since safety, efficacy and quality are essential for drug products, stability studies must be performed. Therefore, degradation studies must be carried out to evaluate the degradation products formed. The active pharmaceutical ingredients 3TC and TDF, as well as the tablets containing the combination of these drugs were subjected to a comprehensive forced degradation. 3TC, TDF and the degradation products were analyzed by a stability-indicating ultra-high performance liquid chromatography (UHPLC) method developed and validated. A C8 (100 x 2.0 mm, 2.2 μm) column and a mobile phase composed of 0.1 M ammonium acetate buffer pH 4.0, acetonitrile and methanol in gradient elution, at 0.5 mL/min, were used. The injection volume was 4 μL and detection was at 260 nm. The method was selective, precise, accurate and linear in the range 0.1-0.6 mg mL-1 for the two drugs. 3TC was degraded in acidic, alkaline and oxidative environment and in the presence of metal ions. Two degradation products were observed. TDF was degraded in the same conditions than those 3TC was labile. In addition, TDF was degraded in neutral condition. Again, two degradation products were formed. Chemical structures were proposed for the degradation products using UHPLC-QTOF/MS. The stability-indicating method developed showed to be useful in stability studies and in the quality control of fixed-dose combination tablets containing 3TC and TDF.